2020
DOI: 10.1016/j.surg.2019.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Use of sensors to quantify procedural idle time: Validity evidence for a new mastery metric

Abstract: Background: Pancreatoduodenectomies at high risk for clinically relevant pancreatic fistula are uncommon, yet intimidating, situations. In such scenarios, the impact of individual surgeon experience on outcomes is poorly understood. Methods: The fistula risk score was applied to identify high-risk patients (fistula risk score 7e10) from 7,706 pancreatoduodenectomies performed at 18 international institutions (2003e2020). For each case, surgeon pancreatoduodenectomy career volume and years of practice were link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…There were no standardized breaks between intubations. Attempts without the box (1-5) always preceded attempts with the box (6)(7)(8)(9)(10).…”
Section: Phase 1 -Impact On Time To Intubationmentioning
confidence: 99%
“…There were no standardized breaks between intubations. Attempts without the box (1-5) always preceded attempts with the box (6)(7)(8)(9)(10).…”
Section: Phase 1 -Impact On Time To Intubationmentioning
confidence: 99%
“…One of the most powerful aspects of our multimodal methodology is that it can be adapted to capture the performance criteria in various medical procedures. To this end, we have collected data from procedures spanning multiple surgical specialties, such as general, cardiothoracic, microsurgery, and gynecology 3,19,28,29 . One of the most important factors that facilitate productive data collection and collaboration is working with principal investigators who have already developed simulators or educational curricula for surgical education in their own fields.…”
Section: Discussionmentioning
confidence: 99%
“…The actual airway mold for both scenarios remained the same. Participants were also verbally instructed that they may experience more difficulty with the burnt airway 19 …”
Section: Further Advances In Using Motion and Video Data For Basic Clinical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Advanced engineering technologies such as sensors and motion tracking have been synchronized with video and used to digitize and quantify specific features of expert and novice procedural strategies. 27,28 Differences in operative performance and strategy can be readily identified and linked to specific video segments. 29 In the urologic surgery literature, Hung et al have demonstrated proof of concept that automated measures such as kinematic data from robotic systems can correlate with outcomes and can differentiate even expert from "super-expert" surgeons performing robotic prostatectomy.…”
Section: The Processmentioning
confidence: 99%